Representation of Gender Found in “English for Nusantara” EFL Textbook - Abdul Fikri; Irwandi (Juliet, 2024)
This research aimed to identify gender representation found in English for Nusantara EFL textbook. This research was qualitative research. The data of this research were collected from English for Nusantara EFL textbook specifically for ninth grade. The researchers adopted a framework form Amini & Birjandi (2012) in analysing the data. The researchers focused on some aspects of gender representation such as visibility, firstness, feminine/ masculine generic construction, activity, and occupation. The finding of this research revealed that there is a gender bias between male and female in the textbook. This imbalance suggests a perpetuation of gender biases that can influence learners' perceptions and expectations regarding gender roles. Educators and curriculum developers must recognize the importance of equitable gender representation to foster an inclusive learning environment. Addressing these biases is essential for promoting gender equality and empowering all students, regardless of gender, to envision a wider range of roles and opportunities.